2014
DOI: 10.1152/ajpgi.00433.2013
|View full text |Cite
|
Sign up to set email alerts
|

Feeding-dependent activation of enteric cells and sensory neurons by lymphatic fluid: evidence for a neurolymphocrine system

Abstract: GW. Feeding-dependent activation of enteric cells and sensory neurons by lymphatic fluid: evidence for a neurolymphocrine system. Am J Physiol Gastrointest Liver Physiol 306: G686 -G698, 2014. First published February 27, 2014 doi:10.1152/ajpgi.00433.2013.-Lymphatic fluid is a plasma filtrate that can be viewed as having biological activity through the passive accumulation of molecules from the interstitial fluid. The possibility that lymphatic fluid is part of an active self-contained signaling process that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 68 publications
(67 reference statements)
1
19
0
Order By: Relevance
“…Extrinsic afferent nerves originating in the nodose ganglia densely innervate the antrum and duodenal lamina propria [55] and also in the lumen of lymphatic lacteals [56]. Williams et al recently demonstrated that GLP-1 receptor-expressing nodose neurons were mostly stretch sensors innervating the stomach, whereas the GPR65-expressing population innervated duodenal villi and responded to luminal nutrients [57**].…”
Section: Tuft Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrinsic afferent nerves originating in the nodose ganglia densely innervate the antrum and duodenal lamina propria [55] and also in the lumen of lymphatic lacteals [56]. Williams et al recently demonstrated that GLP-1 receptor-expressing nodose neurons were mostly stretch sensors innervating the stomach, whereas the GPR65-expressing population innervated duodenal villi and responded to luminal nutrients [57**].…”
Section: Tuft Cellsmentioning
confidence: 99%
“…Williams et al recently demonstrated that GLP-1 receptor-expressing nodose neurons were mostly stretch sensors innervating the stomach, whereas the GPR65-expressing population innervated duodenal villi and responded to luminal nutrients [57**]. In addition to specific receptors associated with EEC-released hormones such as 5-HT, CCK, and GLP-2, afferent neurons possess nutrient receptors, including LPA5, mGluRs, and FFA3 [56;58;59]. Sensory nerves in the subepithelial space likely receive EEC signals and directly detect absorbed nutrients.…”
Section: Tuft Cellsmentioning
confidence: 99%
“…Interestingly, LPA5 (GPR92) is expressed almost exclusively in microglia [ 379 , 380 ] and is barely detectable in astrocytes [ 381 , 382 ]. LPA5 is also expressed by peripheral neurons and their nerves [ 65 , 383 ] as well as by neurons in the spinal cord [ 65 ]. However, we are aware of no publications regarding LPA5 expression in neurons located in other regions of the CNS.…”
Section: Lysophosphatidic Acid Receptormentioning
confidence: 99%
“…Recently, Poole et al [11 •• ] identified LPA5 expression on sensory nerves in the jejunal mucosa, in submucosal and myenteric plexuses, and in primary afferent neurons of dorsal root ganglia of mouse, rat, and human. These authors suggested a novel pathway where molecules, including peptides, in the mesenteric lymphatic fluid (MLF) directly activate LPA5 receptors on sensory nerves.…”
Section: Peptide and Amino Acid Sensingmentioning
confidence: 99%
“…These authors suggested a novel pathway where molecules, including peptides, in the mesenteric lymphatic fluid (MLF) directly activate LPA5 receptors on sensory nerves. MLF may provide signals to comprise a ‘neurolymphocrine’ system in which nerve fibers of the lacteal are part of a visceral sensory system that may function separately from those of the vagus, perhaps through primary spinal afferent nerves [11 •• ]. Irrespective of this, peptone-stimulated GLP-1 release was not reduced in GPR92/93 knockout mice [7 •• ], suggesting that this alternative sensory pathway is less important, than the canonical sensing mechanism, at least in mice.…”
Section: Peptide and Amino Acid Sensingmentioning
confidence: 99%